Language Ideology in Military Arabic Learning: A Case Study of Language Policy at a Military Educational Institution - Nurmala, Mia; Supriadi, Rinaldi; Zafirah, Keysha Shira; Fuadi, Farhan; Anandiar, Iqlima Najmi Amalia (Institut Agama Islam Negeri Curup, 2025)
This study investigates the language ideology that informs policy and practice in military educational institutions, with a particular focus on Arabic instruction for military personnel. It explores how beliefs about Arabic as a strategic foreign language are embedded within institutional policies and pedagogical approaches. Employing a qualitative case study at the Language Education and Training Center under the Indonesia’s Ministry of Defense, data were gathered through document analysis, interviews, and classroom observations. The findings indicate that Arabic is ideologically positioned as a language of strategic significance for international defense cooperation, aligning with the national motto Trigatra Bangun Bahasa. The Arabic curriculum, guided by the Ministry of Defense Regulation No. 1 of 2024, reflects an instrumental ideology that links language learning with defense objectives and intercultural competence. This study underscores the dynamic interplay between ideology, policy, and pedagogy in shaping linguistic competence in military settings. Hence, it contributes to broader discussions on how institutional language policies articulate forms of strategic nationalism in multilingual contexts.